Factors influencing the difference between office and ambulatory blood pressure measurements - G. F. Andreeva; A. D. Deev; V. M. Gorbunov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. То identify psychological predictors and quality of life (QoL) indicators affecting the difference between office and ambulatory blood pressure (BP), as well as the effects of long-term antihypertensive treatment on this difference.Material and methods. The database for 8 studies with similar design was analysed, including the data on 204 patients with arterial hypertension (AH), who took diltiazem, amlodipine, betaxolol, moxonidine, enalapril, lisinopril, metopro-lol, ortelmisartanfor 1—3 months. Mean age ofthe participants was 53,2±8,7 years, mean AH duration — 10,6±8,6 years. At baseline and after the treatment end, 24-hour BP monitoring (BPM), QoL and psychological status (PS) assessment were performed.Results. All medications significantly reduced systolic and diastolic BP (SBP, DBP). The office-ambulatory BP difference negatively correlated with QoL scales IV and H, as well as with PS scales F and 6, being positively correlated with PS scales 3, 4, F, and 7. Metoprolol therapy reduced the office ambulatory BP difference: for SBP — from 12,6±2,8 to 0,8±2,8 mm Hg, for DBP — from 10,4±1,8 to 3,0±1,8 mm Hg. Amlodipine reduced this parameter for SBP from 11,9±3,0 to 3,8±3,0 mm Hg.Conclusion. The office-ambulatory BP difference increased when PS scales 3, 4, K, and 7 increased, and decreased when PS scales F and 6 or QoL scales IV and H decreased. Out of all antihypertensive medications studied, only metoprolol and amlodipine monotherapy significantly reduced the office-ambulatory BP difference.